Magnetic and Electrical Properties of Ni3Te2 Single Crystals Grown by Physical Vapor Transport Technique. Issue 7 (14th July 2022) - Jiang, Wan-Yan; Gao, Li-Xin; Fan, Yiwei; Zhao, Gang; Chen, Fei; Cao, Shixun; Li, Zhe; Ge, Jun-Yi
Abstract : The transition metal tellurides (TMTs) have attracted much attention due to their rich properties in both fundamental research and applications. Among all the TMTs, the study of Ni3 Te2 large single crystals is rare. By using the physical vapor transport technique, Zhe Li, Jun‐Yi Ge, and co‐workers have successfully grown Ni3 Te2 single crystals with unique hexagonal cross section and a tubular shape (see article number 2200037 ). The crystal structure, the electrical transport and magnetic properties, and band structures are investigated in detail. It is revealed that Ni3 Te2 exhibits a metallic behavior with the coexistence of ferromagnetism and antiferromagnetism.